2006
DOI: 10.1021/jp057204s
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of the N-(1-Phenylethyl)-N‘-[3-(triethoxysilyl)propyl]-urea Chiral Stationary Phase in Mixed Alcohol/Water Solvents

Abstract: A theoretical and experimental study of alcohol/water and alcohol/alcohol solvent mixtures near a surface of N-(1-phenylethyl)-N'-[3-(triethoxysilyl)propyl]-urea (PEPU), a Pirkle-type chiral stationary phase, is presented. Molecular dynamics simulations are performed at room temperature for water/methanol, water/1-propanol, water/2-propanol, and methanol/1-propanol solvent mixtures confined between two PEPU surfaces. The interface was also prepared experimentally by attaching the PEPU molecules to atomic force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…2 might have on the partitioning behavior of the protein between solid and liquid phases. Many groups, including our own [40,41], have found that the adhesion forces between the same pair of functional groups can be strongly affected by media of differing polarity, such as the methanol-water mixtures used here. Previous chemical force spectrometric measurements on methyl-and perfluoro-terminated SAMs [42] have shown results similar to those that we see here -the adhesive interactions become smaller by orders of magnitude when the polarity of the solution is decreased.…”
Section: Discussionmentioning
confidence: 92%
“…2 might have on the partitioning behavior of the protein between solid and liquid phases. Many groups, including our own [40,41], have found that the adhesion forces between the same pair of functional groups can be strongly affected by media of differing polarity, such as the methanol-water mixtures used here. Previous chemical force spectrometric measurements on methyl-and perfluoro-terminated SAMs [42] have shown results similar to those that we see here -the adhesive interactions become smaller by orders of magnitude when the polarity of the solution is decreased.…”
Section: Discussionmentioning
confidence: 92%
“…19,20 Here we found that the most important contribution to the forces measured in the CFM experiments is determined by the breaking of hydrogen bonds near the surface and that in an water-alcohol mixture the adhesive interaction decreases rapidly with increasing the alcohol concentration. 20 We also noted that the solvents play an important role in observing chiral discrimination in chemical force spectrometric measurements; the adhesive interaction force for R/R or S/S diaseteromeric complexes in methanol was about 3-4 nN higher than that for R/S or S/R combinations. 19…”
Section: Introductionmentioning
confidence: 88%
“…In another study, the tips were modified with 2,2,2-trifluoro-1-(9-anthryl)ethanol and the samples were derivatized with DNB-phenylglycine, but the adhesive forces did not show a clear chiral discrimination . We have previously studied the CSP N -(1-phenylethyl)- N ′-[3-(triethoxysilyl)propyl]urea (PEPU) in different solvents and solvent mixtures. , Here we found that the most important contribution to the forces measured in the CFM experiments is determined by the breaking of hydrogen bonds near the surface and that in an water−alcohol mixture the adhesive interaction decreases rapidly with increasing the alcohol concentration . We also noted that the solvents play an important role in observing chiral discrimination in chemical force spectrometric measurements; the adhesive interaction force for R / R or S / S diaseteromeric complexes in methanol was about 3−4 nN higher than that for R / S or S / R combinations …”
Section: Introductionmentioning
confidence: 92%
“…These methods and results for achiral separations, with respect to grafting densities, chain alignment, solvent density profiles near the substrate and interface regions, are enlightening also with respect to enantiomeric separations, for example, their simulations in which a chiral selector is covalently tethered to a planar slit pore solid support consisting of tertramethylsilane end caps, with no silanols on the surface. 12 Cann et al have carried out MD simulations of solvent effects on covalently-bonded selectors, in particular PEPU (N-(1-phenylethyl)-N 0 -3-(triethoxysilyl)propyl-urea), 52,53 DNB-leucine ((R)-N-(3,5-dinitrobenzoyl) leucine), DNB-phenyl glycine ((R)-N-(3,5-dinitrobenzoyl)phenylglycine) for solvents of variable composition, 35 proline-based selectors with variable numbers of proline moieties in the same mixed solvents, 40,42 1-(3,5-dinitrobenzamido)-1,2,3,4-tetrahydrophenanthrene or Whelk-O1 in n-hexane/2-propanol, water/methanol, and a supercritical solvent of CO2 and methanol. 36 Their studies describe the detailed nature of the interface for these types of selectors in the solvent systems.…”
Section: Preparing the Interface Solvent Effects On Covalently-bonded Selectorsmentioning
confidence: 99%
“…Cann et al have carried out MD simulations of solvent effects on covalently‐bonded selectors, in particular PEPU ( N ‐(1‐phenylethyl)‐ N ′‐ 3‐(triethoxysilyl)propyl‐urea), 52,53 DNB‐leucine ((R)‐ N ‐(3,5‐dinitrobenzoyl)leucine), DNB‐phenyl glycine ((R)‐ N ‐(3,5‐dinitrobenzoyl)phenylglycine) for solvents of variable composition, 35 proline‐based selectors with variable numbers of proline moieties in the same mixed solvents, 40,42 1‐(3,5‐dinitrobenzamido)‐1,2,3,4‐tetrahydrophenanthrene or Whelk‐O1 in n ‐hexane/2‐propanol, water/methanol, and a supercritical solvent of CO2 and methanol 36 . Their studies describe the detailed nature of the interface for these types of selectors in the solvent systems.…”
Section: Studies On Covalently Bonded Selectorsmentioning
confidence: 99%